Jawabanmu

2014-08-18T19:45:28+07:00
A. (8x+3) - (3x-9) = 8x-3x + 3+9 = 5x + 12
b. (9y^2+y) - (-2y^2-3y) = 9y^2+2y^2 +y+3y = 11y^2 + 4y
c. w(2-2w) = 2w-2w^2
   (2w-2w^2) -(w^2+3w-6) = -2w^2-w^2 +2w-3w -6 =-3w^2 - w - 6
d. (q^2 -3q) - (5q+5q) = q^2 - 3q-5q-5q =q^2 -13q
semoga dapat membantu :)
2014-08-18T19:57:41+07:00
A. (8x + 3)-(3x-9)
= 8x+3-3x+9
= 8x-3x+3+9
= 5x+12
b. (9ykuadrat+y)-(-2ykuadrat-3y)
= 9ykuadrat+y+2ykuadrat+3y
= 9ykuadrat+2ykuadrat+y+3y
= 11ykuadrat+4y
c. [w(2-2w)]-(wkuadrat+3w-6)
[(w.2)-(w.2w)]-(wkuadrat+3w-6)
(2w-2wkuadrat)-(wkuadrat+3w-6)
2w-2wkuadrat-wkuadrat-3w+6
= (-2wkuadrat)-wkuadrat+2w-3w+6
= (-3wkuadrat)+(-1w)+6
d. (qkuadrat-3q)-(5q+5q)
= qkuadrat-3q-5q-5q
= qkuadrat-(-7q)
= qkuadrat +7q